Comparison of hypertonic saline-sodium hydroxide method with modified Petroff’s method for the decontamination and concentration of sputum samples - Chaudhary, SK; Mishra, B (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Tuberculosis is one of the major health problems particularly in developing countries. For definitive diagnosis of pulmonary tuberculosis identification of tubercle bacilli in sputum by microscopy and culture is essential. For decontamination and concentration of sputum, the commonly used method in the laboratory is Modified Petroff’s method but the Hypertonic saline–sodium hydroxide (HS-SH) method is known to be better for detection of Mycobacterium tuberculosis by culture. This study was aimed to compare a novel method for the improvement of decontamination and concentration of sputum samples. MATERIALS AND METHODS: A total of 50 confirmed smear positive sputum samples from pulmonary TB patients who visited at St. John’s Medical College and Hospital during 2009 to 2010, were processed for the decontamination process. Each sample was decontaminated by Modified Petroff’s and HS-SH method separately. Treated samples were cultured in Lowenstein-Jensen media in microbiology laboratory. RESULTS: The culture positive percents of Mycobacterium tuberculosis in the L-J medium treated with HS-SH and Modified Petroff’s method were 84.0% and 70.0%, respectively. A notable feature is that by HS-SH method more samples were positive by 4th week, statistically significant (Chi- square value-11.26 with p-value < 0.05) compare to Modified Petroff’s method. The difference for 3+ grades of L-J growths found slightly higher by Modified Petroff’s method but at lower grades of growths HS-SH method performed better. CONCLUSIONS: HS-SH method is better for the detection of Mycobacterium tuberculosis by culture when compared with the Modified Petroff’s method. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8664 Int J Infect Microbiol 2013;2(3):78-81